HUBUNGAN FREKUENSI KONSUMSI MAKANAN INSTAN DENGAN KEJADIAN HIPERTENSI PADA PENDUDUK BERUSIA ≥ 18 TAHUN DI INDONESIA (ANALISIS DATA RISKESDAS 2018) - Sirait, Rachel Inekeputri; Ronoatmodjo, Sudarto (Jurnal Kesehatan Masyarakat, 2024)
Hypertension or high blood pressure is a condition when a person's blood pressure exceeds normal limits. According to The Basic Health Research in 2018, the prevalence of hypertension in Indonesia reached 34.1%. This figure increased from the previous year, which was 25.8%. Consumption patterns of risky foods such as excess sodium consumption are one of the risk factors for hypertension. One source of sodium comes from instant food. This study aims to determine the relationship between the frequency of instant food consumption and the incidence of hypertension in people aged ≥ 18 years in Indonesia. This study used a cross-sectional study design. The data source used is the 2018 National Basic Health Research secondary data. The research respondents were residents in Indonesia aged ≥18 years. There were 384,556 respondents who met the inclusion and exclusion criteria. Based on the results of the analysis, the prevalence of hypertension was 29.8%. and the proportion of frequency of instant food consumption is 22.1%. There is a significant relationship between the frequency of instant food consumption and hypertension. The group that has a frequent frequency of consuming instant food is 0.78 times (PR=0.785; 95%CI=0.773—0.797) more likely to experience hypertension than the group that has a rare frequency. It was concluded that there is a relationship between the frequency of instant food consumption and the incidence of hypertension in people aged ≥ 18 years in Indonesia.